Two-step sequential blade-coating of high quality perovskite layers for efficient solar cells and modules. Issue 17 (17th April 2020) - Zhang, Junwen; Bu, Tongle; Li, Jing; Li, Hengyi; Mo, Yanping; Wu, Zhengli; Liu, Yifan; Zhang, Xiao-Li; Cheng, Yi-Bing; Huang, Fuzhi
Abstract : A two-step sequential blade-coating process in air to fabricate high-efficiency perovskite solar cells and modules. Abstract : Although perovskite solar cells have achieved an efficiency over 25%, the scalable fabrication of high efficiency and stable large perovskite solar modules is still a big challenge. To date, various up-scaling methods have been developed to deposit large area perovskite films, but most of them are mainly based on the MAPbI3 perovskites and a few on the more stable FA-based perovskites. Here, two-step sequential blade-coating is employed for the scalable fabrication of FA-based perovskite solar cells from ∼0.1 cm 2 devices to 100 cm 2 modules. It is found that a non-volatile solvent having strong coordination and low solubility with PbI2 is beneficial for self-formation of regular nano-porous structured PbI2 films through blade-coating. This continuous porous structure is extremely important for the PbI2 films to be effectively converted to black phase perovskites. Upon further combining with appropriate perovskite seed-assisted growth to improve the crystallinity, a champion efficiency of 20.49% for 0.16 cm 2 devices, an efficiency of 16.54% for 5 × 5 cm 2 perovskite solar modules, and an efficiency of 13.32% for 10 × 10 cm 2 modules are achieved, all with outstanding stability. This indicates the great potential of two-step sequential printing of perovskite films in scalable production.